Applying Project Based Flip Learning Strategy to Improve Students' Reading Comprehension at The Eleventh Social 4 Grades of SMAN 9 Musi Rawas - Liza Anggraini; Ira Maisarah; Syafryadin Syafryadin; Wisma Yunita (Linguistic, English Education and Art (LEEA) Journal, 2022)
One of fundamental language skills that become important ability in academic and social life is reading. One of the elements that can determine whether the students learn English successfully or unsuccessfully comes from the teachers or educators themselves. The teachers decide which approaches, strategies, methods, and techniques will be used to create a classroom environment that is conducive to learning. This creates an environment where students can learn effectively. The research is being done on how to enhance students' reading abilities using project based flip learning strategy. The findings of research on analyzing the applying of Project Based Flip Learning Strategy, the students responded agree for the statements provided in the questionnaire presented. It can be a proven of the assumption of the research that the Project Based Learning Strategy will improve the students’ reading comprehension skill. So, the researcher can conclude that using Project Based Flip Learning Strategy can enhance students' reading understanding skills In Material for reading explanation texts in class eleven social sciences 4 SMAN 9 Musi Rawas. Keywords: Project based Flipped Learning Strategy, Reading Comprehension